Ultrasound-Assisted Extraction of Bioactive Compounds from Tanacetum vulgare L.: Antibacterial and Cytotoxic Evaluation - Burdelnaya, Yelena; Solyanov, Dmitry; Akhmetova, Saule; Pozdnyakova, Yelena (Emerging Science Journal, 2025)
This study investigates ultrasound-assisted extraction (UAE) of bioactive compounds from Tanacetum vulgare L. collected in Central Kazakhstan’s Akmola region, focusing on optimizing extraction parameters, analyzing chemical composition, and evaluating biological activity. The novelty lies in the first comprehensive analysis of T. vulgare populations under the region’s extreme continental climate, known to affect metabolite accumulation. Using 70% ethanol, UAE at 20 minutes provided the highest extraction efficiency, as evidenced by a substantial recovery of phenolic compounds. High-performance liquid chromatography (HPLC) identified key bioactive components – luteolin (6.9 µg/mL), quercetin (5.0 µg/mL), apigenin (1.45 µg/mL), cynaroside (2.7 µg/mL), rutin (1.28 µg/mL), chlorogenic acid (1.1–1.14 µg/mL), and ferulic acid (2.46–2.69 µg/mL) – with extraction time significantly influencing their yield. The antibacterial assessment revealed strong inhibition against Staphylococcus aureus, with a 30-minute flower extract producing an inhibition zone of 34±1.1 mm, surpassing benzylpenicillin (30±1.1 mm). By contrast, weak or no activity was observed against Escherichia coli, Bacillus subtilis, Pseudomonas aeruginosa, and Candida albicans. In cytotoxicity tests using Artemia salina, all extracts – regardless of concentration or duration – resulted in 100% lethality, suggesting potential toxic effects. These findings underscore the impact of Kazakhstan’s harsh ecological conditions on the phytochemical profile of T. vulgare and point to both the plant’s promising pharmacological applications and the need for caution in its use.